The Problem of environmental pollution in modern time is an extended form of the problem of Taboo in ancient societies - A study based on the thoughts of Mary Douglas - Poologanathan, P. (Swamy Vipulananda Institute of Aesthetic Studies, Eastern University, Srilanka, 2017)
Anthropologist Mary Douglas undertook her research into culture from a stance of daily life, As a part of her research on culture, she undertook a field research in 1950, on culture of the people of Congo, which was colonist rule of Belgium. She had discussed in her book, "Purity and Danger" (1966), Taboo and purity, which were considered as cultural elements of those people. Matters that were considered a deviation from routine procedures were noted as Taboo and Uncleanness. The ancient societies used several rites to remove this taboo and uncleanness and purify the society. Mary Douglas had noted in her book that these societies purified themselves with revival rites. In another of her book, "Risk and Culture" (1982), she studies about the environmental pollution problems of modern time, being detached from subjects that were taken for research from ancient Societies. Here, she notes that, the Technical advances achieved in developed countries like America, are found to be aggravating environmental pollution and the environment is being polluted by the class interest of the elite. In her book, "Risk and Culture", she says that the modern society attempt to prevent the Pollution today through several rites (like Environment day and Earth day), just like the ancient societies purified themselves from taboo and impurity through rites (like Sacrifice). The main objective of this study is to establish that the problem of environmental pollution of the modern time is an extended form of problem regarding Taboo that prevailed in the ancient societies through the comparison of Mary Douglas' books, "Purity and Danger" and "Risk and Culture". For this study, Comparative and Analytical methods are utilized and also the data is collected as primary and secondary sources.
Keywords: Taboo; Purity; Sacrifice; Rites; Uncleanness